LEMBAGA KEUANGAN ISLAM BANK - Suryani, Irma (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2015)
The main principle of operation of Islamic banks is based on Islamic shariah laws which are derived from the Quran and Sunnah. Islamic banks have a role as an intermediary (intermediary) between economic units that have excess funds (surplus units), with units other underfunded (deficit units) through banks such excess may be distributed to the parties that need thus providing menfaat to both sides. In Islamic banking, the relationship between the bank and its customers instead of the debtor to the creditor relationship, but a partnership (partner ship) between funders (Sohibulmaal) and manager (mudharib). Therefore, the profit rate of Islamic banks do not only affect the level of good results for shareholders but also affect the results that can be given to customers deposit funds. This partnership is a typical part of the process mechanisms for Islamic banks.Â Prinsip utama operasi bank syariah ini didasarkan pada syariah Islam yaitu hukum-hukum yang bersumber dari alqurâan dan sunnah rasul. Bank syariah mempunyai peran sebagai lembaga perantara (intermediary) antara unit-unit ekonomi yang mengalami kelebihan dana (surplus units), dengan unit-unit yang lain yang mengalami kekurangan dana (devisit units) melalui bank kelebihan tersebut dapat disalurkan kepada pihak-pihak yang memerlukan sehingga memberikan menfaat kepada kedua belah pihak. Dalam Bank syariah, hubungan antara bank dengan nasabahnya bukan hubungan debitur dengan kreditur, melainkan hubungan kemitraan (patner ship) antara penyandang dana (sohibul maal) dengan pengelola (mudharib). Oleh karena itu tingkat laba bank syariah tidak saja berpengaruh terhadap tingkat baik hasil untuk para pemegang saham tetapi juga berpengaruh terhadap bagi hasil yang dapat diberikan kepada nasabah penyimpanan dana. Hubungan kemitraan ini merupakan bagian yang khas dari proses berjalannya mekanisme bank syariah.